THE INFLUENCE OF ENVIRONMENTAL MANAGEMENT ACCOUNTING AND CARBON EMISSION DISCLOSURE ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS MEDIATION IN ENERGY AND BASIC MATERIALS SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Wahyuni, Hilda Fauziah; Mulyasari, Windu; Soleha, Nurhayati (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to analyze the influence of environmental management accounting and carbon emission disclosure on company value mediated by financial performance. This study is important because of increasing awareness of environmental issues and pressure from various stakeholders to be more transparent on environmental issues. The sample in this research is energy and basic materials sector companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The research method used is multiple regression analysis using panel data. The dependent variable in this research is company value. Meanwhile, the independent variables are environmental management accounting and carbon emission disclosure. Financial performance as a mediating variable is measured using the Return on Assets financial ratio. The research results show that environmental management accounting has a significant influence on company value, while carbon emission disclosure does not have a significant influence on company value. Apart from that, financial performance also does not act as a significant mediator in the relationship between environmental management accounting and carbon emission disclosure on company value. This finding may be caused by several factors, including the lack of direct relevance between environmental management accounting and carbon emission disclosure and financial performance, as well as the lack of real follow-up from companies to reduce carbon emissions